2008
DOI: 10.1007/s11695-008-9699-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcome of Patients Admitted to the ICU Following Bariatric Surgery

Abstract: The ICU admission rate in our report is 8%. This study showed that 32 ICU days are needed per 100 diverse bariatric procedures. Most patients are admitted to the ICU for only a few days and the majority of the admissions is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…(12,13,16,17) Research involving 12,062 patients undergoing bariatric surgeries, of whom only 590 (4.90%) were admitted to the ICU postoperatively, showed that this group of patients had a significantly higher mean age and more frequently required an abdominal reoperation. Thus, contrary to what was verified in the present study, both groups had different characteristics, and ICU stay was better justified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(12,13,16,17) Research involving 12,062 patients undergoing bariatric surgeries, of whom only 590 (4.90%) were admitted to the ICU postoperatively, showed that this group of patients had a significantly higher mean age and more frequently required an abdominal reoperation. Thus, contrary to what was verified in the present study, both groups had different characteristics, and ICU stay was better justified.…”
Section: Discussionmentioning
confidence: 99%
“…(12-15) However, international studies show the current preference for avoiding routine ICU hospitalization, which reduces the mean hospital stay, reduces costs and releases beds, which are increasingly scarce, for other patients. (8,16,17) …”
Section: Introductionmentioning
confidence: 99%
“…Also, OSA is related to severe respiratory complications and ICU admission. Reducing costs by identifying and treating risk patients with CPAP and consequently avoiding the expensive use of ICU facilities is desirable [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, preoperative cardiac risk assessment is extremely important, including liberal use of stress echocardiography (82) (because myocardial perfusion imaging requires special tables and apertures that may not accommodate the obese patient). Patients with obesity are emergently admitted to the ICU more commonly than patients without obesity and more commonly for a cardiac-related complication (83). Unfortunately, identifying a cardiac etiology for readmission may go undiagnosed initially (83,84).…”
Section: Postoperative Cardiac Complicationsmentioning
confidence: 99%
“…Patients with obesity are emergently admitted to the ICU more commonly than patients without obesity and more commonly for a cardiac-related complication (83). Unfortunately, identifying a cardiac etiology for readmission may go undiagnosed initially (83,84). In addition, patients with morbid obesity have severely limited cardiorespiratory fitness that is similar to those patients with established severe systolic heart dysfunction (85,86).…”
Section: Postoperative Cardiac Complicationsmentioning
confidence: 99%